MOTIVATION OF TEACHERS TO PARTICIPATE IN PROJECT ACTIVITIES ON PHYSICAL CULTURE IN THE UNIVERSITY CONDITIONS - Goncharuk, Ya.A.; Goncharuk, S.V.; Isaev, I.F.; Nikulina, T.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify measures and specific solutions to increase the motivation of teachers to the technology of project management in the sports and educational space of the university, based on sociological research data. Methodology and organization of the study. The sociological survey "Diagnostics of the management system of the physical culture and educational space of universities" covered seven universities in the Belgorod, Kursk and Lipetsk regions. The survey touched upon the main actors of the physical culture and educational space of the university and their in-depth interviewing using the focus group method. The study involved 300 teachers and researchers of the university, 140 employees of the university administration. The peculiarities of respondents' attitude to the use of the project approach were revealed. Results and conclusions. The technology of project management in the development of the physical culture and educational space of the university can arouse considerable interest on the part of teachers, subject to the implementation of a number of organizational and technological measures proposed by the authors. All projects should be interconnected and form a “ring of projects”, at the same time, each project should be focused on solving a problem regarding the specific disposition of the sports and educational space of the university (values, needs, level of awareness, etc.). It is necessary to form a system for ensuring project activities, which includes: information support; formation of readiness for project activities; skills formation; incentive system. A project management system should be created, which will be based on the principle of interaction between administrative structures and the university community through a system of councils. The criteria for evaluating the effectiveness of project activities have been identified in relation to various groups: 1) student youth; 2) teachers and researchers; 3) employees of the university administration. At the same time, the evaluation system should be based on such criteria as the level of involvement, scale, level of satisfaction.